Effect of plaque staining on oral hygiene of and clinical performance of periodontal non-surgical therapy for patients with periodontitis (菌斑染色对牙周炎患者口腔卫生和基础治疗疗效的影响) - ZHANG Xiaowei (张晓巍); WANG Wei (王威); JING Wudi (靖无迪); YAN Tong (晏桐); TANG Youjia (汤有佳); LI Jiayao (李加尧) (中西医结合护理)
Objective　Methods Forty adult periodontitis patients were involved(twenty in the test group and twenty in the control group, randomly). All patients received systematic periodontal examination, recording and calculating percentage of sites with plaque, probing depth and bleeding on probing, and implement routine oral hygiene instruction at the first visit. The test group received additional plaque staining and individual oral hygiene instruction. Both groups completed supragingival scaling and polishing at the first visit. After 1 week, subgingival scaling and root planning were completed. After 6 weeks, re-evaluation was performed, and oral hygiene and periodontal clinical indicators were recorded and compared. Results The percentage of plaque in test group and control group decreased by (56. 21 ± 14. 64)% and (43. 82 ± 11. 01)% respectively after treatment; The percentage of calculus decreased by(33. 60 ± 11. 01)% and (21. 28 ± 11. 96)% respectively compared with that before treatment. There were also statistically significant differences in the percentage of plaque and calculus between the two groups before and after treatment(P＜0. 001). After treatment, the probing depth of the two groups decreased by (1. 61 ± 0. 96) mm and (0. 86 ± 0. 69) mm, respectively; The percentage of bleeding after probing in the two groups decreased by (49. 51 ± 14. 67) % and (36. 70 ± 15. 40) %, respectively, compared with that before treatment. There were also statistically significant differences in the probing depth and the percentage of bleeding on probing between the two groups before and after treatment, and between the two groups(P＜0. 001). Conclusion The auxiliary application of plaque staining is helpful to improve the oral health status of patients with periodontitis and the clinical performance of periodontal non-surgical therapy. T　o evaluate the clinical effect of plaque staining-assisted routine oral health education on oral hygiene of and clinical performance of periodontal non-surgical therapy for patients with periodontitis. (目的 评估菌斑染色辅助常规口腔卫生宣教方法的临床效果。方法 选取40例拟行牙周基础治疗的成年牙周炎患者, 随机分入试验组和对照组, 各20例。首诊均接受系统牙周检查, 记录和计算菌斑、牙石百分比、探诊深度和探诊后出血并实施常规口腔卫生宣教。试验组额外应用菌斑染色并接受个性化口腔卫生指导。两组均于首诊完成龈上洁治和抛光, 1周后分区段完成龈下刮治和根面平整, 6周后进行再评估, 记录并对比口腔卫生情况和牙周临床指标。结果 治疗后试验组与对照组菌斑百分比较治疗前分别降低(56. 21±14. 64)%和(43. 82±11. 01)%; 牙石百分比较治疗前分别降低(33. 60±11. 01)%和(21. 28±11. 96)%, 两组菌斑和牙石百分比治疗前后的差异和两组间降低值的差异均有统计学意义(P＜0. 001)。治疗后两组探诊深度较治疗前分别降低(1. 61±0. 96) mm和(0. 86±0. 69) mm; 两组探诊后出血百分比较治疗前分别降低(49. 51±14. 67)%和(36. 70±15. 40)%, 两组探诊深度和探诊后出血百分比治疗前后的差异和两组间降低值的差异均有统计学意义(P＜0. 001)。结论 辅助应用菌斑染色有助于改善牙周炎患者的口腔卫生状况和牙周基础治疗疗效。)